2011
DOI: 10.1159/000321733
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Antipyretic Treatment in Stroke: A Pilot Study

Abstract: Background: Fever after acute cerebral injury is associated with unfavorable functional outcome and increased mortality, but there is controversy about the optimal antipyretic treatment. This study investigated an institutional standard operating procedure (SOP) for fever treatment in stroke patients including a sequence of pharmacologic and physical interventions. Methods: A 4-step antipyretic SOP was established for patients with acute cerebral ischemia or hemorrhage and a body temperature ≧37.5°C within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Neither study found associations between ischemic brain temperature and admission stroke severity. The associations between CNL temperature and clinical findings parallel those found for tympanic temperature in the same patients 11 and that others have found for body temperature in other studies 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 summarized in Karaszewski et al 11 The difference in the pattern of brain temperature elevation in the ischemic lesion, combined with the different associations with clinical and imaging features, suggests that the mechanism(s) for early temperature elevation in ischemic brain are different to those which elevate temperature in normal-appearing brain and cause pyrexia. This leads to several important conclusions:

The elevated temperature in ischemic tissue is not directly related to body temperature and possibly not to progression of brain injury, and appears to have a different mechanism to that of body and normal-appearing brain temperature;

that body temperature elevation after ischemic stroke occurs secondary to the systemic (presumably inflammatory) response to brain injury and is reflected in temperature in normal-appearing brain.

…”
Section: Discussionsupporting
confidence: 88%
“…Neither study found associations between ischemic brain temperature and admission stroke severity. The associations between CNL temperature and clinical findings parallel those found for tympanic temperature in the same patients 11 and that others have found for body temperature in other studies 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 summarized in Karaszewski et al 11 The difference in the pattern of brain temperature elevation in the ischemic lesion, combined with the different associations with clinical and imaging features, suggests that the mechanism(s) for early temperature elevation in ischemic brain are different to those which elevate temperature in normal-appearing brain and cause pyrexia. This leads to several important conclusions:

The elevated temperature in ischemic tissue is not directly related to body temperature and possibly not to progression of brain injury, and appears to have a different mechanism to that of body and normal-appearing brain temperature;

that body temperature elevation after ischemic stroke occurs secondary to the systemic (presumably inflammatory) response to brain injury and is reflected in temperature in normal-appearing brain.

…”
Section: Discussionsupporting
confidence: 88%
“…В настоящее время накопился большой опыт купирования дрожи. Для этого эффективно применяются буспирон, меперидин, клонидин, дексмедетомидин, сульфат магния, причем ряд работ показал синергизм эффектов буспирона и меперидина [11]. Кроме того, часто возникают сложности при поддерживании температуры тела на желаемом уровне путем поверхностного охлаждения, в связи с чем высок риск переохлаждения [12].…”
Section: Intensive Care In Diseases Of Nervous Systemunclassified
“…Observational studies like that of Kallmünzer et al [8] might stimulate further research in this field of high clinical significance for acute stroke care. More than 3 decades after Hindfelt's [11] recommendation 'that fever and subfebrility, irrespective of their genesis, should be intensely combated during the early stages of an ischaemic stroke' we need a proven treatment strategy for fever control.…”
mentioning
confidence: 94%
“…Kallmünzer et al [8] investigated the safety of an institutional 4-step protocol using pharmacological and physical interventions in order to enforce post-stroke fever control. When body temperature was 6 37.5 ° C, treatment was started with 1 g paracetamol intravenously (level 1) and in case of nonresponse followed hourly by treatment with 1 g metamizole intravenously (level 2), calf packing (level 3) and finally intravenous infusion of 500 ml of 4 ° C cold saline solution (level 4).…”
mentioning
confidence: 99%